2021
DOI: 10.1002/mnfr.202000780
|View full text |Cite
|
Sign up to set email alerts
|

Three Novel Dietary Phenolic Compounds from Pickled Raphanus Sativus L. Inhibit Lipid Accumulation in Obese Mice by Modulating the Gut Microbiota Composition

Abstract: Scope Although pickled radish is widely consumed worldwide, few studies have investigated the nutritional benefits of bioactive compounds extracted from pickled radish. In this study, the authors investigate the relationship among dietary phenolic compounds, lipid accumulation, and gut microbiota. Method and Results Three phenolic compounds 2,6‐dihydroxyacetophenone (DHAP), 4‐hydroxyphenethyl alcohol (4‐HPEA), and 4‐hydroxybenzaldehyde (HBA) are extracted from pickled radish. LO2 cells treated with free fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…1 It is widely known to people as a raw material for functional food, medicine and cosmetics due to its antioxidant, 2 anti-inflammatory 3 and anticancer properties. 4 LYC has a strong antioxidant capacity due to a large number of conjugated double bonds. 5 It has been shown that LYC is the most efficient biological carotenoid singlet oxygen quencher.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is widely known to people as a raw material for functional food, medicine and cosmetics due to its antioxidant, 2 anti-inflammatory 3 and anticancer properties. 4 LYC has a strong antioxidant capacity due to a large number of conjugated double bonds. 5 It has been shown that LYC is the most efficient biological carotenoid singlet oxygen quencher.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, phenolics are the major active constituents of DLT extracts, which have anti-oxidant, anti-hypoglycemic, anti-hypotensive, anti-depressant, blood lipid regulation, and liver protection effects [5]. Considering their benefits to human health, phenolic compounds are usually used as natural additives in food industry [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…We next used 16S sequencing to investigate how MGE affects gut microbial compositions and diversities in DIO mice. α-Diversity and β-diversity are two key indicators that reflect the differences in gut microbial communities ( 38 , 39 ). We found that the α-diversity of the gut microbiota was increased in DIO mice but was not altered by MGE treatment.…”
Section: Discussionmentioning
confidence: 99%